Evaluation of Calcidol (25(OH)D3) or Combination of Calcidol and Beta-Carotene on Feed Intake, Growth Performance, and Health in High-Risk, Newly Received Beef Heifers - Macie C. Weigand; Zachary M. Duncan; W. Cole Ellis; Colton D. Weir; E. F. Schwandt; A. W. Levy; P. N. Gott; A. J. Tarpoff; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to evaluate the effects on feed intake, growth performance, and health when calcidol [25(OH)D3] or a combination of calcidol and beta-carotene was supplemented in high-risk, newly received growing beef heifers. Study Description: A total of 480 crossbred high-risk heifers (body weight (BW) = 500 ± 35 lb) were fed one of four dietary treatments for a 56-day receiving period. All cattle received a 60 net energy for gain diet limit-fed at 2.2% of BW (dry matter basis). Treatments included: 1) 3,000 IU/head/day added vitamin D3 (Control), 2) 0.5 mg/head/day calcidol; (HyD, DSM Nutritional Products, Plainsboro, NJ; HyD Low); 3) 1.0 mg/head/day calcidol (HyD High); and 4) 1.0 mg/head/day calcidol and 100 mg of beta-carotene (Victus Transition; DSM Nutritional Products, Plainsboro, NJ; HyD + BC). Results: Final BW, average daily gain, gain:feed, and dry matter intake did not differ (P ≥ 0.36) among treatments. Heifers fed HyD High had greater (P < 0.01) serum 25(OH)D3 concentrations than heifers fed HyD Low at days 14, 28, and 56. At days 14, 28, and 56, all heifers supplemented with HyD (HyD Low, HyD High, HyD + BC) had greater (P < 0.01) serum 25(OH)D3 concentrations compared with heifers fed Control. The overall prevalence of respiratory morbidity and mortality was 54.6% and 1.45%, respectively. No treatment differences (P ≥ 0.16) were detected for first, second, or third respiratory morbidity or mortality. Overall, supplementation with calcidol or combination of calcidol and beta-carotene did not affect feed intake, growth performance, or health of high-risk, newly received heifers. The Bottom Line: Calcidol supplementation is the most efficient way to elevate circulating serum 25 hydroxyvitamin D3. However, this study showed no significant differences between treatments in feed intake, growth performance, or health in high-risk, newly receiving beef cattle.
Keywords: high-risk receiving cattle; vitamin D; 25-hydroxy-D3